Climate models - Voldoire, Aurore (Comptes Rendus. Mécanique)
The first climate models have emerged in the 60s and have been continuously developed since then. They have progressively included the representation of all the climate system components: the atmosphere, the ocean, the cryosphere and the biosphere. Inside each component, they have also been enriched by the representation of more processes with the aim of improving their realism. These models are used to make climate projections over the coming century but they are above all a laboratory tool to improve our understanding of the climate system.